Tomorrow's children - Polansky, Daniel (Angry Robot, 2024)
"Tomorrow, the funk descends on Manhattan, a noxious cloud which separates the island from the rest of the world and mutates the population. Some generations on, the surviving population exists amid the rubble of modernity, wearing our cast-off clothing, worshipping celebrities as dim gods and using emojis in place or written language. The Island exists in a state of uneasy peace, with each neighborhood an independent fiefdom, protecting itself with scrap metal spears and Molotov cocktails"--